La inteligencia musical y su importancia en el desarrollo socio-afectivo de los niños y niñas de 4-5 años de la escuela de educación básica “Riobamba” de la provincia de Cotopaxi, cantón Latacunga, parroquia Guaytacama barrio Pilacoto en el periodo 2014-2015 - Almachi Guayta, Silvia Alicia (2015)
The elaborate research work contains very important aspects to improve the Learning-Process of children with the strengthening of musical intelligence that helps define, rhythms and songs to produce tone, stamp, discriminate and expressing the different musical forms. So the students accept and take advantage of recreational activities musicals that are fundamental, this helps get a generating stimulation that will enrich their skills, musical intelligence is evident in language development achieve better results and expose them during his lifetime. The research was done with children of initial education at "Riobamba" High School then detect that the strategy of musical activities was essential to deal with young children exhibited in a fun way embossing a flattering percentage for teaching. The research work based theoretical form as practice taking aspects that allowing developing the manual of musical intelligence, and its importance in the socio-affective area of children showing that man can define these musical activities as a body to solve problems in any field.